Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Improvement of Discontinuous Deformation Analysis Incorporating Implicit Updating Scheme of Friction and Joint Strength Degradation - Ryota Hashimoto; Tomohiro Sueoka; Tomofumi Koyama; Mamoru Kikumoto (Rock Mechanics and Rock Engineering, 2021)

How do surrounding environments influence the electronic and vibrational properties of spheroidene? - Noriyuki Tonouchi; Daisuke Kosumi; Mitsuru Sugisaki; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2015)

Sphingosine 1-phosphate lyase inhibition by 2-acetyl-4-(tetrahydroxybutyl)imidazole (THI) under conditions of vitamin B6 deficiency - Mamoru Ohtoyo; Masakazu Tamura; Nobuo Machinaga; Fumihito Muro; Ryuji Hashimoto (Molecular and Cellular Biochemistry, 2015)

Molecular assembly of Zn porphyrin complexes using synthetic light-harvesting model polypeptides - Tsuyoshi Ochiai; Takahide Asaoka; Tomoya Kato; Shinichiro Osaka; Takehisa Dewa; Keiji Yamashita; Alastair T. Gardiner; Hideki Hashimoto; Mamoru Nango (Photosynthesis Research, 2008)

Electrostatic effect of surfactant molecules on bacteriochlorophyll a and carotenoid binding sites in the LH1 complex isolated from Rhodospirillum rubrum S1 probed by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Probing binding site of bacteriochlorophyll a and carotenoid in the reconstituted LH1 complex from Rhodospirillum rubrum S1 by Stark spectroscopy - Katsunori Nakagawa; Satoru Suzuki; Ritsuko Fujii; Alastair T. Gardiner; Richard J. Cogdell; Mamoru Nango; Hideki Hashimoto (Photosynthesis Research, 2008)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Noggin and basic FGF were implicated in forebrain fate and caudal fate, respectively, of the neural tube-like structures emerging in mouse ES cell culture - Shunmei Chiba; Manae S. Kurokawa; Hideshi Yoshikawa; Ritsuko Ikeda; Mitsuhiro Takeno; Mamoru Tadokoro; Hiroaki Sekino; Takuo Hashimoto; Noboru Suzuki (Experimental Brain Research, 2005)